Toward the Next Generation of Negative Symptom Assessments: The Collaboration to Advance Negative Symptom Assessment in Schizophrenia - Blanchard, Jack J. (Oxford University Press, 2011)
Negative symptoms in schizophrenia are related to poor functional outcome, persistent over time, a source of burden for caregivers, and only minimally responsive to currently available medications. A major challenge to developing efficacious interventions concerns the valid and reliable assessment of negative symptoms. In a recent consensus statement on negative symptoms, a central recommendation was the need to develop new assessment approaches that address the limitations of existing instruments. In the current report, we summarize the background and rationale for the Collaboration to Advance Negative Symptom Assessment in Schizophrenia (CANSAS). The CANSAS project is an National Institute of Mental Health-funded multisite study that is constructing a next-generation negative symptom scale, the Clinical Assessment Interview for Negative Symptoms (CAINS). The CAINS is being developed within a data-driven iterative process that seeks to ensure the measure’s reliability, validity, and utility for both basic psychopathology and treatment development research.